Analysis of the hydroelastic effect on a container vessel using coupled BEM–FEM method in the time domain. (20th April 2020) - Datta, R.; Guedes Soares, C.
ABSTRACT: This paper investigates numerically the effect of flexibility for a container ship in calculation vertical bending moment and shear force etc. For this purpose, the hydrodynamic forces are determined using a lower order panel method based on 3D transient free surface Green's function. For the solution of the structural problem, 1D FEM is developed in the time domain. The Panel code and the FEM code are coupled in the time domain through the body boundary condition. The structural deformation and velocity at each section in each time step are calculated using the Newmark–Beta method. Structural deflection, vertical bending moment, shear force, dynamic pressure distribution along the hull for S175 Ship are computed for both rigid and flexible structure and compared to check the influence of the flexibility. From the results, it is seen that the structural flexibility plays a very important role for bending moment and shear force calculations.